2022
DOI: 10.1002/ece3.8521
|View full text |Cite
|
Sign up to set email alerts
|

Fitness, risk taking, and spatial behavior covary with boldness in experimental vole populations

Abstract: Individuals of a population may vary along a pace‐of‐life syndrome from highly fecund, short‐lived, bold, dispersive “fast” types at one end of the spectrum to less fecund, long‐lived, shy, plastic “slow” types at the other end. Risk‐taking behavior might mediate the underlying life history trade‐off, but empirical evidence supporting this hypothesis is still ambiguous. Using experimentally created populations of common voles (Microtus arvalis)—a species with distinct seasonal life history trajectories—we aime… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 126 publications
0
6
0
Order By: Relevance
“…In enclosure studies, a semi‐field area is built in order to study an effect in the absence of confounding variables (Boonstra and Krebs, 1977; Gaines et al., 1979; Schauber et al., 1997; Hahne et al., 2011; Jochym and Halle, 2013; Eccard et al., 2022). Voles and other small mammals have been the most frequently studied species.…”
Section: Integrated Exposure and Effect Assessment Tiers For Birds An...mentioning
confidence: 99%
“…In enclosure studies, a semi‐field area is built in order to study an effect in the absence of confounding variables (Boonstra and Krebs, 1977; Gaines et al., 1979; Schauber et al., 1997; Hahne et al., 2011; Jochym and Halle, 2013; Eccard et al., 2022). Voles and other small mammals have been the most frequently studied species.…”
Section: Integrated Exposure and Effect Assessment Tiers For Birds An...mentioning
confidence: 99%
“…Recent growth in the study of inter-individual variation in behaviour [4][5][6], however, revealed that behaviour is not entirely flexible [5], and that individuals differ consistently in behavioural traits within a population [7]. Further, this consistent variation has fitness consequences [8,9]. For the success of biological invasions of animals, two contrasting concepts have been suggested: behavioural invasion syndromes and behavioural flexibility [10], i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Further, knowing that in many species males and females differ in space use and dispersal tendency [32][33][34] we assumed that the sexes may be exposed to differential selection pressures during the process of population expansion. With space use being closely related to behavioural traits [9,25], selection on space use and dispersal traits may produce spatial sorting patterns in personality traits differing among males and females. We therefore (c) investigated interactions of sex and expansion zone on the behaviour of the phenotyped individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Recent growth in the study of inter-individual variation in behavior (4, 5, 6), however, revealed that behavior is not completely flexible (5) and that individuals differ consistently within a population (7). Further, this consistent variation has fitness consequences (8, 9). For the success of biological invasions of animals, two contrasting concepts have been suggested: behavioral invasion syndromes and behavioral flexibility (10).…”
Section: Main Textmentioning
confidence: 99%